English as Lingua Franca; A Threat to Multilingualism - Yoga Prihatin (Cakrawala: Jurnal Pendidikan, 2014)
Linguistic imperialism is often seen in the context of cultural imperialism. This article is intended to describesome teories of English as a lingua franca that can be a threat to multilingualism to some extent. Theendangerd language project predicts that half of the world 6,500 languages by the end of the century andthat the major reason of people learning national language and lingua franca (Han Rausing 2008). Thefollowing three princliples would help retain local languages on the other hand validate and promotemultilingualism on the other; First, wherever possible, the mother tounge should be used as the mediuminstruction; other wise a local language shoud be used. Second, English can be happily be delayed until thelater years of primary school. Thridly, the goal of Learners of English in multilingual and lingua franca settingshould be multilingual performance and profeciency, not an idealized native-like profeciency.